Respostas
respondido por:
1
xA = coordenada x de A
xB = coordenada x de B
yA = coordenada y de A
yB = coordenada y de B
dAB = distância de A a B
(dAB)² = (xB - xA)² + (yB - yA)²
(dAB)² = (1 - 3)² + (4 - 7)²
(dAB)² = (-2)² + (-3)²
(dAB)² = 4 + 9
(dAB)² = 13
dAB = √13
xB = coordenada x de B
yA = coordenada y de A
yB = coordenada y de B
dAB = distância de A a B
(dAB)² = (xB - xA)² + (yB - yA)²
(dAB)² = (1 - 3)² + (4 - 7)²
(dAB)² = (-2)² + (-3)²
(dAB)² = 4 + 9
(dAB)² = 13
dAB = √13
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás